Negotiating Identity and the Politics of Chinese Ethnic Assimilation in Clara Ng's Novel "Dimsum Terakhir" - Zhou Yin Lin; Wiyatmi Wiyatmi; Deng Yao (JENTERA: Jurnal Kajian Sastra, 2026)
This study aims to analyze the representation of Chinese identity in Clara Ng's novel Dimsum Terakhir. The study uses a qualitative approach with a text analysis design based on Stuart Hall's cultural identity theory and a sociological perspective of literature to uncover the construction of ethnic identity through narratives, characters, and social contexts in literary works. Data collection techniques were carried out through literature studies using the reading and note-taking method. The researcher conducted intensive and repeated readings of the text (close reading) to identify relevant data, then grouped them based on thematic categories. Data analysis refers to the stages of qualitative analysis according to Creswell (2015), including organizing data, coding, interpreting themes, and drawing interpretive conclusions by considering the social, historical, and ideological contexts of the text. The results of the study indicate that Chinese identity in the novel Dimsum Terakhir is not singular and static but rather a dynamic and continuously negotiated social construction. The representation of identity is evident through identity politics, such as changes in name, religion, and citizenship status, which reflect structural pressures and assimilation practices. In addition, discrimination and stereotypes that emerge in social interactions indicate the existence of unequal power relations. Culturally, traditions such as Chinese New Year celebrations and the consumption of dim sum are maintained despite restrictions placed on private spaces. This research confirms that the novel "Dimsum Terakhir" represents Chinese identity as a space for social, political, and psychological negotiation, while also providing implications for strengthening multiculturalism and respecting cultural diversity in Indonesia. Abstrak Penelitian ini bertujuan untuk menganalisis representasi identitas Tionghoa dalam novel “Dimsum Terakhir” karya Clara Ng. Penelitian menggunakan pendekatan kualitatif dengan desain analisis teks yang didasarkan pada teori identitas budaya Stuart Hall dan perspektif sosiologi sastra untuk mengungkap konstruksi identitas etnis melalui narasi, tokoh, dan konteks sosial dalam karya sastra. Teknik pengumpulan data dilakukan melalui studi pustaka dengan metode baca dan catat. Peneliti melakukan pembacaan teks secara intensif dan berulang (close reading) untuk mengidentifikasi data yang relevan, kemudian mengelompokkannya berdasarkan kategori tematik. Analisis data mengacu pada tahapan analisis kualitatif menurut Creswell (2015), meliputi pengorganisasian data, pengodean, interpretasi tema, dan penarikan simpulan secara interpretatif dengan mempertimbangkan konteks sosial, historis, dan ideologis teks. Hasil penelitian menunjukkan bahwa identitas Tionghoa dalam novel “Dimsum Terakhir” tidak bersifat tunggal dan statis, melainkan merupakan konstruksi sosial yang dinamis dan terus dinegosiasikan. Representasi identitas tampak melalui politik identitas, seperti perubahan nama, agama, dan status kewarganegaraan, yang mencerminkan tekanan struktural serta praktik asimilasi. Selain itu, diskriminasi dan stereotip yang muncul dalam interaksi sosial menunjukkan adanya relasi kuasa yang tidak setara. Dalam aspek budaya, tradisi seperti perayaan Imlek dan konsumsi dimsum tetap dipertahankan meskipun mengalami pembatasan dalam ruang privat. Penelitian ini menegaskan bahwa novel “Dimsum Terakhir” merepresentasikan identitas Tionghoa sebagai ruang negosiasi sosial, politik, dan psikologis sekaligus memberikan implikasi bagi penguatan multikulturalisme dan penghargaan terhadap keberagaman budaya di Indonesia.